2016
DOI: 10.1111/1348-0421.12347
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Pseudomonas aeruginosa phage KPP21 belonging to family Podoviridae genus N4‐like viruses isolated in Japan

Abstract: Bacteriophages (phages) belonging to the family Podoviridae genus N4-like viruses have been used as therapeutic agent in phage therapy against Pseudomonas aeruginosa infections. P. aeruginosa phage KPP21 was isolated in Japan, and phylogenetically investigated the phages belonging to this viral genus. Morphological and genetic analyses confirmed that phage KPP21 belongs to the family Podoviridae genus N4-like viruses. Moreover, phylogenetic analyses based on putative DNA polymerase and major virion protein sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…To assess the characterization of AM.P2 with respect to previously documented phages, a comparative study of the AM.P2 genome was done. Phylogenetic analysis suggests that the phage is closely related to LUZ7 and KPP21 (19,20), two phages isolated from geographically distant regions (Belgium and Japan, respectively) but that nevertheless share high levels of homology (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…To assess the characterization of AM.P2 with respect to previously documented phages, a comparative study of the AM.P2 genome was done. Phylogenetic analysis suggests that the phage is closely related to LUZ7 and KPP21 (19,20), two phages isolated from geographically distant regions (Belgium and Japan, respectively) but that nevertheless share high levels of homology (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…Genome sequencing revealed them to be N4-like, sharing a similar gene order and possessing all 18 core genes that were found among all N4-like members. For phage therapy applications involving the treatment of Pseudomonas aeruginosa murine infections, N4-like phages have been deemed to be safe and effective [ 45 ]. This suggested that the three identified phages could be good candidates for biocontrol applications.…”
Section: Discussionmentioning
confidence: 99%
“…The G7-like phages The E. coli phage N4, the prototype species of the group of N4-related viruses was a database orphan for many years (Kazmierczak et al 2002). However, over the last decade, numerous N4-like viruses that infect Gram-negative bacteria were isolated and sequenced (Faidiuk et al 2017;Golomidova et al 2007;Cai et al 2015;Patel et al 2015;Li et al 2016;Ma et al 2016;Shigehisa et al 2016;Bhattacharjee et al 2017;Katharios et al 2017;Buttimer et al 2018), and for reviews see (Chan et al 2014;Wittmann et al 2015). The N4-related sequences are also ubiquitous in human fecal metagenomes and viromes (Waller et al 2014).…”
Section: Discussionmentioning
confidence: 99%